Neurotropic Cutaneous Malignancies: Case Report on Keratinocyte Derived Malignancies of the Head and Neck With Perineural Invasion - Ahn, Grace Sora; Hinds, Brian; Kolb, Frederic; Reisenauer, Amy K.; Soon, Seaver L.; Sepahdari, Ali R.; Bollin, Kathryn B.; Park, Soo J. (Frontiers in Oncology, 2022)
Background: The recent addition of immunotherapy as a treatment modality to surgery and radiation has vastly improved disease control for patients with keratinocyte-derived carcinomas (KC) that are incurable with local therapies alone. With the advent of immune checkpoint inhibitors (ICPi) in non-melanoma skin cancers comes diagnostic and therapeutic challenges when considering treatment strategies for patients presenting with cutaneous perineural invasion (cPNI) of locally advanced KC of the head and neck. Objectives: We report four cases that convey the diagnostic and therapeutic complexity of managing patients with neuropathic symptoms from cutaneous perineural invasion in KC of the head and neck. We also discuss an updated review regarding immunotherapies and perineural invasion within KC management. Conclusion: Patients presenting with symptoms suspicious for cPNI warrant an expanded diagnostic evaluation to correlate neurological findings with neurotropic spread of disease. While nerve biopsies can be precarious in sensitive areas, a history of skin cancer and clinical presentation suggestive of neurotropism may be enough to pursue timely management in the form of surgery, radiation, and/or systemic therapy given each patient’s individual priorities, comorbidities, and prognosis. When adding ICPi as a treatment modality for patients with disease not amenable to local therapies, the potential for immune-related adverse events must be considered. A multi-disciplinary review and approach to the management of patients with KC and cPNI is essential for obtaining optimal patient outcomes.